2017
DOI: 10.1371/journal.pone.0181508
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of factor H-Binding protein sequence to the cross-reactivity of meningococcal native outer membrane vesicle vaccines with over-expressed fHbp variant group 1

Abstract: Factor H-binding protein (fHbp) is an important meningococcal vaccine antigen. Native outer membrane vesicles with over-expressed fHbp (NOMV OE fHbp) have been shown to induce antibodies with broader functional activity than recombinant fHbp (rfHbp). Improved understanding of this broad coverage would facilitate rational vaccine design. We performed a pair-wise analysis of 48 surface-exposed amino acids involved in interacting with factor H, among 383 fHbp variant group 1 sequences. We generated isogenic NOMV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The reason for this could be linked to multiple factors not yet fully elucidated, including that GMMA present key antigens in their native conformation and orientation. As with many previous studies, in this study we have confirmed that N. meningitidis fHbp, when presented on the GMMA surface, is much more immunogenic than fHbp alone or simply physically mixed with GMMA [ 27 , 29 , 34 , 36 ]. Indeed, fHbp on GMMA elicited a higher antibody response than the controls despite a lower fHbp amount and, importantly, induced bactericidal titers post I, differently from the controls, and titers much higher than the controls after re-injection.…”
Section: Discussionsupporting
confidence: 90%
“…The reason for this could be linked to multiple factors not yet fully elucidated, including that GMMA present key antigens in their native conformation and orientation. As with many previous studies, in this study we have confirmed that N. meningitidis fHbp, when presented on the GMMA surface, is much more immunogenic than fHbp alone or simply physically mixed with GMMA [ 27 , 29 , 34 , 36 ]. Indeed, fHbp on GMMA elicited a higher antibody response than the controls despite a lower fHbp amount and, importantly, induced bactericidal titers post I, differently from the controls, and titers much higher than the controls after re-injection.…”
Section: Discussionsupporting
confidence: 90%
“…The polymerase incomplete primer extension (PIPE) cloning method [40] was used to insert fHbp (variant 1-ID5 from Neisseria meningitidis serogroup A strain) [41] into a pGEX-derived plasmid, carrying the sequence encoding the leader peptide for secretion of E. coli OmpA. The Escherichia coli HK-100 strain was used for cloning and plasmid generation and was grown in Luria-Bertani (LB) broth at 37 • C. Ampicillin was used at the final concentration of 100 µg/mL.…”
Section: Heterologous Antigen Expression and Gmma Preparationmentioning
confidence: 99%
“…For instance, when N. meningitidis OMVs displaying the antigenic porin protein PorA were examined in comparison to purified PorA protein, a humoral immune response was elicited in response to both candidate vaccines, but only the PorA-containing OMVs induced bactericidal antibodies [ 141 ]. The functional immune response induced by OMVs over-expressing fHbp is similar to that induced by > 10-fold higher fHbp administered in recombinant form, suggesting that the native conformation and self-adjuvant properties of OMV have a great impact in the immune response induced [ 142 ]. OMVs naturally released from a recombinant African N. meningitidis W strain with deleted capsule locus, attenuated LPS toxicity ( lpxL1 mutant), improved OMV yield ( gna33 mutant) and with overexpressed fHbp v.1 have been proposed as an affordable vaccine with broad coverage against strains from all main serogroups currently causing meningococcal meningitis in sub-Saharan Africa [ 38 ].…”
Section: Omvs Compared To Classical Vaccinesmentioning
confidence: 99%